KEGIATAN BIMBINGAN TEKNIS BIDANG PARIWISATA (TOUR GUIDE) KABUPATEN TUBAN - Nugroho, Truli; Prakoso, Yusak; Djong, Alexander Mario Retto (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The aim of this community service is to provide additional knowledge and Technical Guidance in the field of Tourism (Tour Guide) in Tuban Regency. The target is tourism sector actors (Tour Guides) in Tuban Regency. This activity will really help tourism sector actors to obtain professional certificates as mandated by Law Number 13 of 2003 concerning Employment mandating the formation of a National Professional Certification Agency and East Java Province Regional Regulation Number 4 of 2022 concerning the Empowerment of independent Tour Guides as well as to carry out competency certification work for workers, whether they come from job training graduates and/or experienced workers. The funds for the activities that will be carried out are socialization and training. The results of this activity produce tourism actors who are competent in their field, supported by evidence of a Competency Certificate in the field being tested.